REMOTE LABORATORY AS CONCEPTUAL MODEL OF BLENDED LEARNING - Kozic, Antoni; Macerauskas, Eugenijus; Sakalys, Paulius (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Practice shows that the best built and maintain by the knowledge, is based on and secured personal work experience. Source of expertise can be carried out e-laboratory theoretical and practical experiments. The study key is the development of the system will hamper its inappropriate use. There is a lack of e-tools that enable students to deal with the challenge, problem or phenomenon monitoring experiments t. y. entering or selecting the initial data. New technology, especially electronic, progress is very important because it allows the development of continuing education, distance education, the democratization of it, adapting to people with different capabilities and needs. Discussed problem is creating a different type of laboratory. The key novelty is that it is not a virtual laboratory based on software tools, but the real remote-controlled electronics lab. Produced simplified conceptual model for remote laboratory experiments and demonstration. The article describes a real remote e-laboratory designed and applied in Vilniaus kolegija/University of Applied Sciences as an experimental practical method for distance learning.